2012
DOI: 10.1111/j.1440-1819.2012.02319.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obsessive–compulsive symptoms in Tourette's syndrome on neuropsychological performance

Abstract: Aim: Although inconsistencies in neuropsychological impairments in Tourette's syndrome (TS) have been discussed with respect to comorbid disorders, such as obsessive-compulsive disorder, few studies have focused on the specific dimensions of obsessive-compulsive symptoms (OCS) related to TS, such as aggression and symmetry. The aim of this study was to explore the impact of specific TS-related OCS on neuropsychological performance.Methods: A series of neuropsychological tasks examining attention and executive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…TS and OCD-related RB, tics and compulsions, have been associated with a dysfunction of cortico-striato-thalamo-cortical circuits, consistent with the hypothesis that obsessive-compulsive symptoms and tics might be part of the same spectrum [12,20]. The corticostriatal circuits are multiple parallel, segregated feedback circuits with outputs from striatum targeting primary motor areas, and specific pre-motor and prefrontal cortical areas.…”
Section: Tourette Syndrome and Obsessive-compulsive Disordersupporting
confidence: 70%
“…TS and OCD-related RB, tics and compulsions, have been associated with a dysfunction of cortico-striato-thalamo-cortical circuits, consistent with the hypothesis that obsessive-compulsive symptoms and tics might be part of the same spectrum [12,20]. The corticostriatal circuits are multiple parallel, segregated feedback circuits with outputs from striatum targeting primary motor areas, and specific pre-motor and prefrontal cortical areas.…”
Section: Tourette Syndrome and Obsessive-compulsive Disordersupporting
confidence: 70%
“…In adults with TS, few studies assessed sustained attention. Normal CPT performance was found [ 79 ] and, as reported before, studies using a D2 cancellation task did not find an increased omission rate [ 56 ]. However, impairments were found in a highly demanding letter cancellation task [ 57 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 77%
“…The picture is less clear regarding other inhibition tasks, such as the Stroop task. On the one hand, several studies reported intact Stroop performance in children [ 69 , 86 , 91 , 144 , 148 , 163 , 164 , 165 , 166 ] and adults [ 57 , 79 , 91 , 107 , 123 , 145 , 167 ] with TS. On the other hand, impaired Stroop performance has also been found in TS children [ 61 , 168 ] and adults [ 34 , 56 , 93 , 97 , 99 ].…”
Section: A Review Of Neuropsychological Functioning In Tsmentioning
confidence: 99%
“…Some comorbidities -such as chronic tics or Tourette's syndrome -that are prevalent among OCD patients may be associated with distinct neuropsychological deficits (Eddy et al, 2009). In fact, it has been indicated that cases of comorbid OCD and Tourette's present with more substantial cognitive deficits, over and above the ones that are thought to characterize each disorder separately (Matsuda et al, 2012). In addition, only a minority of studies assessed and reported the presence of personality disorders, some of which may be associated with a distinct profile of neuropsychological deficits.…”
Section: Additional Considerationsmentioning
confidence: 98%